Equity of physical characteristics between adolescent males and females participating in single- or mixed-sex sport - Krause, L. M.; Naughton, G. A.; Benson, A. C.; Tibbert, S. (The Journal of Strength and Conditioning Research, 2018)
Policies on single- or mixed-sex junior sports participation continue to be challenged publically and legally. Often challenges relate to perceptions of size and performance variability between adolescent males and females, yet the evidence base behind these challenges lacks recent review and rigor. Physical performance was compared between males and females from 2 groups of younger (<13 years, n = 109, 67% females, 33% males) and older (=13 years, n = 108, 43% females, 57% males) adolescents. Using a cross-sectional design, adolescents were tested for speed, strength, power, and endurance. No sex differences were found for most of the physical test results in the <13 years age group, although males showed greater endurance (p = 0.020) and upper-body strength (p = 0.010) than females. However, among adolescents aged =13 years, males scored better than females in all physical tests, without exception (p > 0.05). Further explorations comparing how many females in the same age grouping shared test results equal to or greater than the top third of males were fewer in the older than younger age group. Equality of participation in mixed-sex sport becomes more difficult to guarantee for older adolescents when results from generic sport-related physical test performances are considered.